1996
DOI: 10.1128/aem.62.6.2013-2021.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of In Vivo Reporter Systems for Gene Expression and Biosensor Applications Based on luxAB Luciferase Genes

Abstract: Advances in genetic engineering methods have allowed the development of an increasing number of practical and scientific applications for bioluminescence with lux genes cloned from a variety of organisms. Bioluminescence derived from the shortened lux operon (luxAB genes) is a complex process, and applications seem to be proliferating in advance of an understanding of the underlying biochemical processes. In this report, we describe a two-phase kinetic behavior of the light emission which must be properly take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The same has been reported when luxABCDE genes from P. luminescens were integrated into the E. coli chromosome . The availability of fatty aldehyde has been reported to be the limiting factor in P. luminescens luciferase‐linked BL emission . We also added a fatty aldehyde (decanal) into a growth medium for recombinant E. coli –lux and observed that the BL signal increased to the level indicated by the increase of the OD in the logarithmic phase (data not shown).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The same has been reported when luxABCDE genes from P. luminescens were integrated into the E. coli chromosome . The availability of fatty aldehyde has been reported to be the limiting factor in P. luminescens luciferase‐linked BL emission . We also added a fatty aldehyde (decanal) into a growth medium for recombinant E. coli –lux and observed that the BL signal increased to the level indicated by the increase of the OD in the logarithmic phase (data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…We have previously used luxAB genes from V. harveyi in E. coli . The problem with this construct was that during the logarithmic growth phase the BL signal elevated considerably more than indicated by OD signal and at the beginning of the stationary phase BL emission collapsed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to maintain the pH, oxygen and temperature constant and to study the influence of the bioluminescent strains, their growth stage and growth medium on the spectral emission. Although tetradecanal is the natural aldehyde in the natural bioluminescence reaction (27), decanal was supplied in our experiments as previously mentioned for its practical use (28). From our results, there was no difference in the spectral emission between natural or recombinant cells or between Gram-positive and Gram-negative strains.…”
Section: Discussionmentioning
confidence: 56%
“…All five RR‐dependent promoters‐ lux (luciferase) fusions were inserted into pLUX vector (Table ) (Blouin et al . ; Burton et al . ).…”
Section: Methodsmentioning
confidence: 99%